The Relationship between comorbidities and the high mortality rate of Covid 19 patients at Kepatihan Health Centre, Gresik - Nugroho, Muhammad Yanuar; Kusumaningtyas, Maria Juliati; Herliani, Olivia (Calvaria Medical Journal, 2024)
Background: The Covid-19 pandemic has a broad impact on health and society, comorbidities or comorbidities can be a risk factor for covid-19 infection and can worsen the condition of people who have been infected with COVID-19. Aim: The purpose of this study is the relationship between comorbidities and the high mortality rate of Covid-19 patients at the Kepatihan Health Centre, Gresik in 2019-2021. Methods: This study used a cross sectional analytical observational research design, the population in this study were people in the Kepatihan Gresik Health Centre working area who had Covid-19 in 2019-2021, totalling 809 people. Calculated using the slovin formula with a simple random sampling technique, so that the sample size was 75 respondents. The study used secondary data and the analysis used was the chi square test.. Result: The results showed that most of the respondents in this study were respondents with Covid 19 patient deaths having comorbidities, namely 43 respondents or 57.3%, most of the respondents in this study were respondents with no hypertension, namely 55 respondents or 73%, most of the respondents in this study were respondents with no DM, namely 51 respondents or 68%, and most of the respondents in this study were respondents with no Asthma, namely 63 respondents or 84% The conclusion of the study is that there is a relationship between comorbidities and the high mortality rate of Covid-19 patients at Kepatihan Health Centre, Gresik in 2019-2021 because it has a p-value <0.05. Conclusion: Based on the results of the research and discussion in the chapter, it can be concluded that there is a relationship between hypertension, diabetes mellitus (DM), and asthma with cases of death due to Covid-19 at the Gresik District Health Center in 2019-2021.